2009
DOI: 10.5694/j.1326-5377.2009.tb02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients expect transparency in doctors’ relationships with the pharmaceutical industry

Abstract: Objective: To seek the views of patients attending general practice about doctors’ interactions with the pharmaceutical industry and their wishes for disclosure of this information. Design, setting and participants: 906 patients attending three general practices in metropolitan Sydney during October –November 2007 completed an 18‐item anonymous survey exploring their perceptions of doctors’ competing interests. Results: Most patients (76%) were unaware of any relationship their doctor may have with pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 25 publications
4
56
1
2
Order By: Relevance
“…13 Perhaps some might interpret receiving money from industry as beneficial, and do not mind if their physician is involved in innovation or consulting 7,8 whereas others may interpret this as undue influence. 2 Grady, et al demonstrated that a percentage of their patient cohort felt that the payments physicians received was a “private matter.” 14 Some patients want full disclosure of financial relationships, 15 although others have reported in studies that they would still participate in research regardless of the involvement of their doctors in industry. 7,8,16 In a contrasting study, Kim et al, found that 64–87% of subjects in a research trial wanted to know the financial influences of the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…13 Perhaps some might interpret receiving money from industry as beneficial, and do not mind if their physician is involved in innovation or consulting 7,8 whereas others may interpret this as undue influence. 2 Grady, et al demonstrated that a percentage of their patient cohort felt that the payments physicians received was a “private matter.” 14 Some patients want full disclosure of financial relationships, 15 although others have reported in studies that they would still participate in research regardless of the involvement of their doctors in industry. 7,8,16 In a contrasting study, Kim et al, found that 64–87% of subjects in a research trial wanted to know the financial influences of the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…[7, 50, 52, 53, 55, 58, 60, 63] The response rate was not reported for three studies [49, 57, 64] and varied across the remaining from 8.8% to 96%. The single qualitative study was judged to have met most of the CASP checklist.…”
Section: Resultsmentioning
confidence: 99%
“…Distrust is also increasingly expressed towards scientific and medical research, the foundation of the medical profession, because of the influence of pharmaceutical industry and physician‐researcher conflicts of interest . Patients are not necessarily made aware of doctor's pharmaceutical company engagements or financial incentives to enrol patients into funded trials . Frequent high‐profile cases of academic misconduct drive an increasing number of journal article retractions .…”
Section: Trust In Medical Education and Health Carementioning
confidence: 99%